THE SHIFTING PARADIGM IN INDONESIAN FILM DISTRIBUTION DURING THE COVID-19 PANDEMIC - Muhammad Yunus Patawari; Dyah Rachmawati Sugiyanto (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Cinemas or movie theaters are one of the industries that can hold its own amidst digital disruption. As a means of distribution and exhibition of conventional films, cinemas have the ability to adapt themselves to various digital innovations; starting from the audio-visual projection device, ticketing, payment system to 3D technology. The existence and survival of a cinema rely on two factors, namely film distribution and moviegoer factors, the COVID-19 pandemic has shifted these two factors. If previously movie distribution and moviegoing occurred conventionally, the two activities have shifted considerably to online distribution/streaming. This study analyzed the paradigm shift in film distribution and moviegoing during and after the pandemic using a “three-stage model of theory building” as an analytical tool which is part of the descriptive-qualitative methodology. The results showed that the COVID-19 pandemic is an anomaly that is shifting the paradigm in conventional film distribution as evidenced by the fact that it is not new media that pose a threat to the existence of cinemas, but the insubstantial social functions and cinema activities during the pandemic. There are five factors why cinemas will continue to develop as a film distribution and exhibition medium post COVID-19: cinema adaptation, big screen sensation, entertainment and social values, historical values, and economic factors.